The Human In Vivo Biomolecule Corona onto PEGylated Liposomes: A Proof‐of‐Concept Clinical Study. Issue 4 (28th November 2018) - Hadjidemetriou, Marilena; McAdam, Sarah; Garner, Grace; Thackeray, Chelsey; Knight, David; Smith, Duncan; Al‐Ahmady, Zahraa; Mazza, Mariarosa; Rogan, Jane; Clamp, Andrew; Kostarelos, Kostas
Abstract: The self‐assembled layered adsorption of proteins onto nanoparticle (NP) surfaces, once in contact with biological fluids, is termed the "protein corona" and it is gradually seen as a determinant factor for the overall biological behavior of NPs. Here, the previously unreported in vivo protein corona formed in human systemic circulation is described. The human‐derived protein corona formed onto PEGylated doxorubicin‐encapsulated liposomes (Caelyx) is thoroughly characterized following the recovery of liposomes from the blood circulation of ovarian carcinoma patients. In agreement with previous investigations in mice, the in vivo corona is found to be molecularly richer in comparison to its counterpart ex vivo corona. The intravenously infused liposomes are able to scavenge the blood pool and surface‐capture low‐molecular‐weight, low‐abundance plasma proteins that cannot be detected by conventional plasma proteomic analysis. This study describes the previously elusive or postulated formation of protein corona around nanoparticles in vivo in humans and illustrates that it can potentially be used as a novel tool to analyze the blood circulation proteome. Abstract : A biomolecule corona self‐assembles around blood‐circulating nanoparticles in humans. PEGylated doxorubicin‐encapsulated liposomes, recovered from the blood circulation of ovarian carcinoma patients, are coated with a mixture of proteins, including low‐molecular‐weight and low‐abundance proteins that cannot be detected by conventional proteomic analysis. The biomolecule corona fingerprint has the potential to be used as a tool to analyze the blood proteome.